A comparative analysis of forced migration: Cold War versus post-Cold War eras - Bilol Buzurukov; Byeong Wan Lee (Kiel Institute for the World Economy (IfW), 2016)
This paper conducts a comparative analysis of forced international migration between two historical periods: 1969-1990 representing the Cold War era, and 1991-2012, the post-Cold War era. The determinants of refugee migration over the two periods are assessed and compared using a panel data analysis for a sample of 125 countries. In order to control for unobserved country-specific effects and the joint endogeneity of the explanatory variables, the Arellano-Bond Dynamic Panel GMM (Generalized Method of Moments) estimator is used. Overall, the results suggest that significant changes have taken place with both the set of explanatory variables and their individual impact on refugee migration over time. Also noteworthy is the significance of the two flight facilitators - the Internet and the telecommunication devices - included in the model to explain the refugee migration dynamics during the post-Cold War period.
Keywords: F22; D74; L86; L96; C23; 330; Forced Migration; War and Conflicts; Flight Facilitators; GMM Dynamic Panel Data Analysis